Effect of 7-nitroindazole, a neuronal nitric oxide synthase inhibitor, on behavioral and physiological parameters - Brožíčková, C; Mikulecká, A; Otáhal, J (Physiological research, 2014)
The role of brain derived nitric oxide in the physiology and behavior remains disputable. One of the reasons of the controversies might be systemic side effects of nitric oxide synthase inhibitors. Therefore, under nNOS inhibition by 7-nitroindazole (7-NI) we carried out recordings of blood gasses, blood pressure and spontaneous EEG in conscious adult rats. Locomotion and spontaneous behavior were assessed in an open field. In addition skilled walking and limb coordination were evaluated using a ladder rung walking test. The blood gas analysis revealed a significant increase in pCO(2) 180 min and 240 min after the application of 7-NI. The power and entropy decreased simultaneously with a shift of the mean frequency of the spontaneous EEG toward slow oscillations after 7-NI treatment. The thresholds of evoked potentials underwent a significant drop and a trend towards a slight increase in the I-O curve slope was observed. 7-NI significantly suppressed open field behavior expressed as distance moved, exploratory rearing and grooming. As for the ladder rung walking test the 7-NI treated animals had more errors in foot placement indicating impairment in limb coordination. Therefore our findings suggest that 7-NI increased cortical excitability and altered some physiological and behavioral parameters.
Keywords: Behavior, Animal; Indazoles; Electroencephalography; Male; Rats, Wistar; Evoked Potentials, Motor; indazoly; elektroencefalografie; mužské pohlaví; Enzyme Inhibitors; potkani Wistar; motorické korové centrum; Nitric Oxide Synthase Type I; Time Factors; Exploratory Behavior; Animals; Motor Cortex; krevní tlak; zvířata; pohybová aktivita; synthasa oxidu dusnatého, typ I; časové faktory; Blood Gas Analysis; Blood Pressure; Motor Activity; chování zvířat; motorické evokované potenciály; inhibitory enzymů; pátrací chování; analýza krevních plynů